Exploring Career Management Competencies in Work Based Learning (WBL) Implementation - Ali, Azita; Marwan, & Hazlina (Journal of Technical Education and Training, 2019)
Graduates’ employability is a commonly highlighted issue in tertiary education due to today’s job market that highly expects the limited vacancies to be filled with competitive and competent graduates. Higher education institutions play a significant role in ensuring and understanding the skills that are needed by the graduates to meet the demand of the professional industry; hence, better job opportunity for the graduates. Work Based Learning (WBL) is one of the platforms for students to gain actual working experience in addition to developing career management competencies to prepare for starting a career. The purpose of this study is to explore the career management competencies that students can master through WBL. This study is a qualitative study that uses analysis of documents and interviews as the primary methods of data collection. Document analysis has been conducted to explore the key elements of competence from the theoretical and literary perspective. Semi-structured interviews were carried out on five selected research experts from various backgrounds and positions in the WBL implementation in polytechnics. Coding and analysis process were conducted based on the recorded transcript of the interview. The collected data were analysed based on the themes that answered the research questions. This study has identified 20 sub-elements covering three key elements of career management competency in the implementation of WBL, namely learning and work exploration, career development, and personal management. The findings of this study are intended to be used as the basis for an effective application of career education in the WBL implementation.